The Concept Of Destiny and Its Relationship With Human Will And Freedom - Abdullaev Sarvar Sabitovich (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article discusses the concept of destiny and its relationship with human will and freedom, exploring the various descriptions of destiny provided by Islamic scholars from different periods and schools of thought. The views of various Islamic sects, such as Sunni, Shia, Qadariyya, Jabariyya, Mu'tazila, Jahmiyya, and Karamiya regarding destiny, are examined. Additionally, the article investigates the views of the two major Sunni theological schools: Maturidi and Ash'ari, analyzing their similarities and contradictions. The author provides scholarly conclusions based on the relationship between the concept of destiny and the notions of secularism and religiosity in contemporary society.